2011
DOI: 10.1073/pnas.1005066107
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of induced colonic inflammation byLactobacillus acidophilusdeficient in lipoteichoic acid

Abstract: Imbalance in the regulatory immune mechanisms that control intestinal cellular and bacterial homeostasis may lead to induction of the detrimental inflammatory signals characterized in humans as inflammatory bowel disease. Induction of proinflammatory cytokines (i.e., IL-12) induced by dendritic cells (DCs) expressing pattern recognition receptors may skew naive T cells to T helper 1 polarization, which is strongly implicated in mucosal autoimmunity. Recent studies show the ability of probiotic microbes to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
187
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(214 citation statements)
references
References 62 publications
(59 reference statements)
12
187
1
7
Order By: Relevance
“…However, bacterial components such as glycolipids may be important for signalling between some probiotics and host. For example, certain Lactobacillus species in which capsular lipoteichoic acid is absent or D-alanine depleted, switch from being pro-to anti-inflammatory 16,17 in vivo and in vitro, and, with respect to visceral pain in rats, to being antinociceptive 18 .…”
mentioning
confidence: 99%
“…However, bacterial components such as glycolipids may be important for signalling between some probiotics and host. For example, certain Lactobacillus species in which capsular lipoteichoic acid is absent or D-alanine depleted, switch from being pro-to anti-inflammatory 16,17 in vivo and in vitro, and, with respect to visceral pain in rats, to being antinociceptive 18 .…”
mentioning
confidence: 99%
“…Celles-ci activent alors des lymphocytes T régulateurs permettant un contrôle de l'inflammation intestinale dans un modèle de colite expérimen-tale chez la souris [11]. Les chercheurs avaient ainsi postulé que cette protéine glycosylée pourrait être reconnue par la lectine de type C DC-SIGN, exprimée par les cellules dendritiques, dont on sait qu'elle contrôle la régulation des réponses immunitaires [12].…”
Section: Lactobacillus Acidophilus Un Futur Outil Thérapeutique Dansunclassified
“…Cependant, chez les patients obèses, la fréquence des lymphocytes iNKT dans le tissu adipeux omental diminue significativement [5]. Des expériences effectuées avec des modèles murins suggèrent que les lymphocytes iNKT ont une fonction régulatrice anti-inflammatoire dans le tissu adipeux [11]. La diminution des lymphocytes iNKT au cours de l'obé-sité contribuerait à la perte de l'homéos-tasie dans le tissu adipeux.…”
Section: Lymphocytes Inkt Et Lymphocytes Maitunclassified
“…[10][11][12] Analyzed mechanisms suggested that the induction of regulatory IL-10 C DCs and functional Tregs, activation of pErk1/2, and the downregulation of critical downstream signals (Akt1, p38) 13 are key elements involved in the amelioration of murine colitis in our models. [10][11][12][13][14] Furthermore, this L. acidophilus strain lacking LTA significantly diminished inflammation-promoting colonic polyposis in the Apc lox468 x TS4-Cre mouse model via the regulation of proinflammatory innate and T cell subsets.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Analyzed mechanisms suggested that the induction of regulatory IL-10 C DCs and functional Tregs, activation of pErk1/2, and the downregulation of critical downstream signals (Akt1, p38) 13 are key elements involved in the amelioration of murine colitis in our models. [10][11][12][13][14] Furthermore, this L. acidophilus strain lacking LTA significantly diminished inflammation-promoting colonic polyposis in the Apc lox468 x TS4-Cre mouse model via the regulation of proinflammatory innate and T cell subsets. 9 Thus, we theorized that the cross-talk between a specific surface molecule expressed by the LTAdeficient L. acidophilus, called SlpA, with intestinal innate cells (e.g., DCs) not only suppresses pathogenic inflammation, but also potentially modulates the expression of epigenetically-regulated, colorectal cancer (CRC)-associated genes, 15 and restores gut homeostasis to ablate colonic polyps.…”
Section: Introductionmentioning
confidence: 99%